Blockchain Based System for Secure File Sharing and Activity Logging - Ch. Lokesh,; Balasathuragiri. T, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the digital age, ensuring the security and integrity of file sharing and activity logging systems is paramount. This paper presents a Blockchain-Based System for Secure File Sharing and Activity Logging, designed to address the critical challenges of data confidentiality, integrity, and traceability. By leveraging blockchain technology, our system provides an immutable and decentralized ledger that enhances the security of file exchanges and logs user activities with unparalleled transparency and trust. The system employs smart contracts to automate and enforce access control, while cryptographic techniques ensure data encryption and integrity. This approach mitigates risks associated with unauthorized access, data tampering, and system breaches. Through detailed implementation and performance evaluation, we demonstrate that our blockchain-based solution significantly improves the security and reliability of file sharing and logging processes compared to traditional systems. This innovation not only fortifies data protection but also offers a scalable framework adaptable to various applications, from enterprise environments to personal data management.